Inorganic-organic hybrid coating and preparation method thereof, insulating coating for battery core
Through the design of the inorganic-organic hybrid coatings, the chemical bonds of modified acrylic dispersal and modified silicone solution are used to solve the problem of insulation and pressure and low production efficiency of the battery insulation coating, and realize high density and denseness and denseness and efficiency. Stable insulation performance.
Patent Information
- Application Number
- CN202311678624.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-08
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-12-08
AI Technical Summary
In the production and application of existing battery cell insulating coatings, there are problems such as unstable insulation voltage resistance, complex curing process, low production efficiency, and no insulating water-based coatings for battery cells.
Inorganic-organic hybrid coating is used, which is prepared by the mixed reaction of component A and component B. Component A includes methyltrialkoxysilane, etc., and component B includes modified silica sol and modified acrylic dispersion. The surface hydroxyl groups of the modified acrylic dispersion and the silicon hydroxyl groups in the modified silica sol are dehydrated and condensed to form a strong chemical bond, thereby improving the density of the coating.
The high density of the coating is realized, the stability of the insulation performance is improved, the effect of high temperature and chemical media is resisting, and a good affinity is formed with the aluminum plate, which enhances the adhesive strength.
Smart Images

Figure CN117625042B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to an inorganic-organic hybrid coating and a preparation method thereof, and an insulating coating for a battery core. Background Art
[0002] In recent years, new energy vehicles have been greatly developed. As one of the three major parts of electric vehicles, the battery pack is composed of a series of small cylindrical batteries or square battery packs. Due to the internal structure, the shell of cylindrical batteries and square batteries is often charged or prone to leakage. For safety reasons, they must be wrapped and isolated with a layer of insulating material.
[0003] The traditional solution in the industry is to apply a layer of insulating film, and the common materials are PET / PI films with adhesive backing. However, due to the insufficient strength of the adhesive backing, the strength of the battery group connection is very low; in addition, the lamination process is complicated and prone to bubbles, which will cause partial discharge in actual application, causing safety hazards; and during transportation and application, it is easy to cause damage when encountering hard objects, and the industry is increasingly criticized.
[0004] In recent years, advanced manufacturers in the industry have begun to use post-curing insulating materials, commonly known as insulating coatings for battery cells. The process materials currently used are: (1) powder coatings; (2) UV coatings; (3) water-based coatings; Powder coatings must be coated with at least 150μm, and individual powder particles are melted at high temperature. The gas (air, water vapor, etc.) under the coating is discharged to reach the surface of the coating for leveling, and then cross-linked to form a coating film. However, in the actual production process, individual powder particles are prone to not melting, and the gas is not completely overflowed, resulting in unstable insulation withstand voltage; UV coatings are limited by their curing method, and high-film thickness paints cannot be completely cured. The actual production process is complicated, and the production efficiency and yield rate are low.
[0005] The construction process of water-based paint is simple, but there is currently no insulating water-based paint specifically for battery cells. Summary of the invention
[0006] The invention provides an inorganic-organic hybrid coating and a preparation method thereof, and an insulating coating for a battery core, to solve the problem.
[0007] In order to solve the above technical problems, the present invention provides an inorganic-organic hybrid coating, characterized in that it comprises: a component A and a component B are mixed and reacted; wherein the component A is prepared by mixing the following raw materials in parts by weight: 70 to 90 parts of methyltrialkoxysilane, 0 to 10 parts of diphenyldialkoxysilane, 0 to 10 parts of tetraalkoxysilane, 0 to 10 parts of γ-aminopropyltriethoxysilane and 0.5 to 3 parts of a catalyst; the component B is prepared by mixing the following raw materials in parts by weight: 50 to 60 parts of modified silica sol; 80 parts, 20-50 parts of modified acrylic dispersion and 1.5-3.5 parts of functional additives; the modified silica sol comprises the following components in parts by mass: 94-96 parts of weak alkaline silica sol, 1-3 parts of vinyl trialkoxy silane and 1-3 parts of γ-methacryloxypropyl trialkoxy silane; wherein the modified acrylic dispersion is obtained by polymerization reaction of monomers including methyl methacrylate, butyl acrylate, styrene, isobornyl methacrylate, hydroxyethyl methacrylate and dimethylbisacrylamide.
[0008] In yet another aspect, the present invention further provides an insulating coating for a battery core, comprising the inorganic-organic hybrid coating as described above.
[0009] In a third aspect, the present invention also provides a method for preparing the insulating coating for the battery cell as described above, which comprises the following steps: step S1, pre-preparing component A and component B; step S2, preparing an inorganic-organic hybrid coating after mixing, stirring and curing; step S3, coating the inorganic-organic hybrid coating on the aluminum plate of the battery cell, and curing to form an insulating coating for the battery cell.
[0010] The beneficial effect of the present invention is that the inorganic-organic hybrid coating and its preparation method, and the insulating coating for the battery cell of the present invention modify the acrylic dispersion, and use the hydroxyl groups on its surface to dehydrate and condense with the silanol groups in the modified silica sol to form a strong chemical bond, so that the coating exhibits better density on a macro scale, and is not easily affected by external factors such as high temperature and chemical media, which may cause damage to the coating and affect the insulation performance. At the same time, it also forms good affinity with the aluminum plate, playing a bridging role.
[0011] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practicing the present invention.
[0012] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0014] Figure 1 It is the infrared spectrum of the inorganic-organic hybrid coating of the present invention. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] The present invention provides an inorganic-organic hybrid coating, which is characterized by comprising: a component A and a component B, wherein the component A is prepared by mixing the following raw materials in parts by weight: 70-90 parts of methyltrialkoxysilane, 0-10 parts of diphenyldialkoxysilane, 0-10 parts of tetraalkoxysilane, 0-10 parts of γ-aminopropyltriethoxysilane and 0.5-3 parts of a catalyst; and the component B is prepared by mixing the following raw materials in parts by weight: 50-80 parts of modified silica sol, 0-10 parts of modified silica sol and 0.5-10 parts of modified silica sol. The present invention relates to a novel modified silica sol comprising 20 to 50 parts of a weak alkaline acrylic dispersion and 1.5 to 3.5 parts of a functional additive; the modified silica sol comprises the following components in parts by weight: 94 to 96 parts of a weakly alkaline silica sol, 1 to 3 parts of vinyl trialkoxy silane, and 1 to 3 parts of γ-methacryloxypropyl trialkoxy silane; wherein the modified acrylic dispersion is obtained by polymerization of monomers including methyl methacrylate, butyl acrylate, styrene, isobornyl methacrylate, hydroxyethyl methacrylate, and dimethylbisacrylamide.
[0017] like Figure 1 As shown, the infrared spectrum of the inorganic-organic hybrid coating shows corresponding characteristic peaks.
[0018] In this embodiment, specifically, the molecular formula of the modified acrylic dispersion is:
[0019]
[0020] Among them, a, b, d, e, f, g, h, j, i are any natural numbers between 1 and 20; c is 5.
[0021] In this embodiment, specifically, the synthetic formula of the modified acrylic dispersion is:
[0022]
[0023] in
[0024] The initiator is any one of ammonium persulfate, potassium persulfate and sodium persulfate.
[0025] In this embodiment, specifically, the inorganic part is mainly an inorganic polymer composed of siloxane bonds (-Si-O-Si-) the same as quartz, and the bond energy of its Si-O bond is 451KJ.mol-1, while the bond energy of the CC bond of the traditional organic coating is 345KJ.mol-1. It has better coating density and is not easily affected by external factors such as high temperature and chemical media, which may cause coating damage and insulation failure. The organic part is mainly acrylic emulsion, and its surface hydroxyl groups dehydrate and condense with silicon hydroxyl groups to form a strong chemical bond, and at the same time has good affinity with the aluminum plate, playing the role of a "bridge".
[0026] In this embodiment, specifically, in the component A, the methyltrialkoxysilane is methyltrimethoxysilane or methyltriethoxysilane; the diphenyldialkoxysilane is diphenyldimethoxysilane or diphenyldiethoxysilane; the tetraalkoxysilane is tetramethoxysilane or tetraethoxysilane; and the catalyst is formic acid, acetic acid, citric acid or a mixture thereof.
[0027] In this embodiment, specifically, in the component B, the vinyl trialkoxysilane is vinyl trimethoxysilane or vinyl triethoxysilane; and the γ-methacryloxypropyl trialkoxysilane is γ-methacryloxypropyl trimethoxysilane or γ-methacryloxypropyl triethoxysilane.
[0028] In this embodiment, specifically, the acrylic dispersion is a hydroxy acrylic dispersion, wherein the hydroxyl content (in solid content) is 1.8-4%.
[0029] In this embodiment, specifically, the functional additives are defoaming agents, wetting and leveling agents, anti-sagging agents, and hand feeling agents.
[0030] In yet another aspect, the present invention further provides an insulating coating for a battery core, comprising the inorganic-organic hybrid coating as described above.
[0031] In this embodiment, specifically, the insulation withstand voltage of the battery cell with the insulation coating is ≥3500VDC, 60s; the leakage current is <0.1mA; and the bonding strength with the structural adhesive is >10Mpa.
[0032] In a third aspect, the present invention also provides a method for preparing the insulating coating for the battery cell as described above, which comprises the following steps: step S1, pre-preparing component A and component B; step S2, preparing an inorganic-organic hybrid coating after mixing, stirring and curing; step S3, coating the inorganic-organic hybrid coating on the aluminum plate of the battery cell, and curing to form an insulating coating for the battery cell.
[0033] The method used to detect coating performance is as follows:
[0034] Withstand voltage: Cover the surface of the battery cell with insulating coating and conductive foam to test the insulation withstand voltage;
[0035] Leakage current: 3500V DC, 60s;
[0036] Butt strength: Test butt strength according to ASTM D3163;
[0037] Bond Strength: Bond strength was tested according to ASTM D1002 standard.
[0038] Example 1
[0039] Preparation of modified acrylic dispersion
[0040] 20g of methyl methacrylate, 40g of butyl acrylate, 5g of styrene, 25g of isobornyl methacrylate, 10g of hydroxyethyl methacrylate, 2g of dimethylbisacrylamide, 0.9g of emulsifier sodium dodecyl sulfate, 50g of deionized water, and 0.3g of ammonium persulfate are added to a pre-emulsification kettle and emulsified for 30-40min to obtain an emulsion without stratification; then 20g of the emulsion, 60g of deionized water, 2g of the emulsifier, and 0.4g of the buffer sodium bicarbonate are added to a polymerization reactor, the temperature is raised to 78-80°C for reaction for 20-30min, and the remaining emulsion and 0.45g of ammonium persulfate initiator are dripped, and the dripping is completed in 3-4h; then the polymerization reactor is heated to 85-90°C and kept for reaction for 1-2h, and the temperature is lowered to 45-50°C and ammonia water is added to adjust the pH value of the reaction system to between 6 and 7. The modified acrylic acid dispersion is thus obtained.
[0041] Example 2
[0042] Preparation of modified silica sol
[0043] 2 parts by mass of vinyltrimethoxysilane and 2 parts by mass of γ-methacryloxypropyltrimethoxysilane were added to 96 parts by mass of weakly alkaline silica sol HS-30 at one time, stirred, heated to 65°C for reaction for 0.5h, cooled to 40°C, filtered and packaged to obtain the modified silica sol.
[0044] Example 3
[0045] Preparation of component A: 85 parts by mass of commercially available analytically pure methyltrimethoxysilane, 5 parts by mass of diphenyldimethoxysilane, 5 parts by mass of tetramethoxysilane, 5 parts by mass of γ-aminopropyltriethoxysilane and 1.5 parts by mass of acetic acid are sequentially added into a stirring barrel and stirred evenly to obtain component A.
[0046] Preparation of component B: Add 70 parts by mass of the modified silica sol prepared in Example 1, 10 parts by mass of a modified acrylic dispersion having a hydroxyl value of 4.0%, 0.2 parts by mass of a defoamer, 0.6 parts by mass of a wetting and leveling agent, 0.5 parts by mass of an anti-sagging agent and 0.6 parts by mass of a feel agent into a stirring barrel in sequence and stir evenly to obtain component B.
[0047] Preparation of coating: Add component A and component B into a mixing barrel in a ratio of 1:2, stir at 500 r / min for 40 min at room temperature, and filter through a 500-mesh filter to obtain the coating for aluminum panels.
[0048] Coating preparation: The aluminum plate was polished to 240 mesh and then dusted. A handheld spray gun was used to control the film thickness to about 40μm, pre-dried at 50℃ for 10min, and then cured at 160℃ for 30min to obtain the insulating coating for the battery cell.
[0049] Example 4
[0050] Preparation of component A: 85 parts by mass of commercially available analytically pure methyltrimethoxysilane, 5 parts by mass of diphenyldimethoxysilane, 5 parts by mass of tetramethoxysilane, 5 parts by mass of γ-aminopropyltriethoxysilane and 1.5 parts by mass of acetic acid are sequentially added into a stirring barrel and stirred evenly to obtain component A.
[0051] Preparation of component B: Add 70 parts by mass of the modified silica sol prepared in Example 1, 20 parts by mass of a modified acrylic dispersion having a hydroxyl value of 4.0%, 0.2 parts by mass of a defoamer, 0.6 parts by mass of a wetting and leveling agent, 0.5 parts by mass of an anti-sagging agent and 0.6 parts by mass of a feel agent into a stirring barrel in sequence and stir evenly to obtain component B.
[0052] Preparation of coating: Add component A and component B into a mixing barrel in a ratio of 1:2, stir at 500 r / min for 40 min at room temperature, and filter through a 500-mesh filter to obtain the coating for aluminum veneer.
[0053] Coating preparation: The aluminum plate was polished to 240 mesh and then dusted. A handheld spray gun was used to control the film thickness to about 40μm, pre-dried at 50℃ for 10min, and then cured at 160℃ for 30min to obtain the insulating coating for the battery cell.
[0054] Example 5
[0055] Preparation of component A: 85 parts by mass of commercially available analytically pure methyltrimethoxysilane, 5 parts by mass of diphenyldimethoxysilane, 5 parts by mass of tetramethoxysilane, 5 parts by mass of γ-aminopropyltriethoxysilane and 1.5 parts by mass of acetic acid are sequentially added into a stirring barrel and stirred evenly to obtain component A.
[0056] Preparation of component B: Add 70 parts by mass of the modified silica sol prepared in Example 1, 30 parts by mass of a modified acrylic dispersion having a hydroxyl value of 4.0%, 0.2 parts by mass of a defoamer, 0.6 parts by mass of a wetting and leveling agent, 0.5 parts by mass of an anti-sagging agent and 0.6 parts by mass of a feel agent into a stirring barrel in sequence and stir evenly to obtain component B.
[0057] Preparation of coating: Add component A and component B into a mixing barrel in a ratio of 1:2, stir at 500 r / min for 40 min at room temperature, and filter through a 500-mesh filter to obtain the coating for aluminum panels.
[0058] Coating preparation: The aluminum plate was polished to 240 mesh and then dusted. A handheld spray gun was used to control the film thickness to about 40μm, pre-dried at 50℃ for 10min, and then cured at 160℃ for 30min to obtain the insulating coating for the battery cell.
[0059] Example 6
[0060] Preparation of component A: 85 parts by mass of commercially available analytically pure methyltrimethoxysilane, 5 parts by mass of diphenyldimethoxysilane, 5 parts by mass of tetramethoxysilane, 5 parts by mass of γ-aminopropyltriethoxysilane and 1.5 parts by mass of acetic acid are sequentially added into a stirring barrel and stirred evenly to obtain component A.
[0061] Preparation of component B: Add 70 parts by mass of the modified silica sol prepared in Example 1, 50 parts by mass of a modified acrylic dispersion having a hydroxyl value of 4.0%, 0.2 parts by mass of a defoamer, 0.6 parts by mass of a wetting and leveling agent, 0.5 parts by mass of an anti-sagging agent and 0.6 parts by mass of a feel agent into a stirring barrel in sequence and stir evenly to obtain component B.
[0062] Preparation of coating: Add component A and component B into a mixing barrel in a ratio of 1:2, stir at 500 r / min for 40 min at room temperature, and filter through a 500-mesh filter to obtain the coating for aluminum panels.
[0063] Coating preparation: The aluminum plate was polished to 240 mesh and then dusted. A handheld spray gun was used to control the film thickness to about 40μm, pre-dried at 50℃ for 10min, and then cured at 160℃ for 30min to obtain the insulating coating for the battery cell.
[0064] Example 7
[0065] Preparation of component A: 85 parts by mass of commercially available analytically pure methyltrimethoxysilane, 5 parts by mass of diphenyldimethoxysilane, 5 parts by mass of tetramethoxysilane, 5 parts by mass of γ-aminopropyltriethoxysilane and 1.5 parts by mass of acetic acid are sequentially added into a stirring barrel and stirred evenly to obtain component A.
[0066] Preparation of component B: Add 70 parts by mass of the modified silica sol prepared in Example 1, 60 parts by mass of a modified acrylic dispersion having a hydroxyl value of 4.0%, 0.2 parts by mass of a defoamer, 0.6 parts by mass of a wetting and leveling agent, 0.5 parts by mass of an anti-sagging agent and 0.6 parts by mass of a feel agent into a stirring barrel in sequence and stir evenly to obtain component B.
[0067] Preparation of coating: Add component A and component B into a mixing barrel in a ratio of 1:2, stir at 500 r / min for 40 min at room temperature, and filter through a 500-mesh filter to obtain the coating for aluminum veneer.
[0068] Coating preparation: The aluminum plate was polished to 240 mesh and then dusted. A handheld spray gun was used to control the film thickness to about 40μm, pre-dried at 50℃ for 10min, and then cured at 160℃ for 30min to obtain the insulating coating for the battery cell.
[0069] The insulating coatings of the battery cells prepared in Examples 3-7 were subjected to relevant performance tests, and the data are summarized in Table 1.
[0070] Table 1
[0071]
[0072] In this embodiment, specifically, it can be seen from Table 1 that when the mass fraction of the modified acrylic dispersion is less than 20 parts, the bonding strength is affected, and when the mass fraction is greater than 50 parts, the leakage current is affected. Embodiment 5 is the best embodiment.
[0073] In summary, the inorganic-organic hybrid coating and its preparation method, and the insulating coating for battery cells of the present invention modify the acrylic dispersion, and use the hydroxyl groups on its surface to dehydrate and condense with the silanol groups in the modified silica sol to form a strong chemical bond, so that the coating exhibits better density on a macro scale, and is not easily affected by external factors such as high temperature and chemical media, which may cause damage to the coating and affect the insulation performance. At the same time, it also forms good affinity with the aluminum plate, playing a bridging role.
[0074] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. An inorganic-organic hybrid coating, characterized in that: include: It is prepared by mixing component A and component B; in Component A is prepared by mixing the following raw materials in parts by weight: 70-90 parts of methyltrialkoxysilane, 0-10 parts of diphenyldialkoxysilane, 0-10 parts of tetraalkoxysilane, 0-10 parts of γ-aminopropyltriethoxysilane and 0.5-3 parts of catalyst; Component B is prepared by mixing the following raw materials in parts by weight: 50-80 parts of modified silica sol, 20-50 parts of modified acrylic dispersion and 1.5-3.5 parts of functional additives; The modified silica sol comprises the following components in parts by weight: 94-96 parts of weak alkaline silica sol, 1-3 parts of vinyl trialkoxy silane, and 1-3 parts of γ-methacryloxypropyl trialkoxy silane; wherein The modified acrylic dispersion is obtained by polymerization of monomers including methyl methacrylate, butyl acrylate, styrene, isobornyl methacrylate, hydroxyethyl methacrylate, and dimethylbisacrylamide; The molecular formula of the modified acrylic dispersion is: ; in a, b, d, e, f, g, h, j, i are any natural numbers between 1 and 20; c is 5; The acrylic dispersion is a hydroxy acrylic dispersion, wherein the hydroxy content accounts for 1.8 to 4% of the solid content; The catalyst is formic acid, acetic acid, citric acid or a mixture thereof.
2. The inorganic-organic hybrid coating according to claim 1, characterized in that: The synthetic formula of the modified acrylic dispersion is: ;in The initiator is any one of ammonium persulfate, potassium persulfate and sodium persulfate.
3. The inorganic-organic hybrid coating according to claim 1, characterized in that: In the component A, the methyltrialkoxysilane is methyltrimethoxysilane or methyltriethoxysilane; the diphenyldialkoxysilane is diphenyldimethoxysilane or diphenyldiethoxysilane; The tetraalkoxysilane is tetramethoxysilane or tetraethoxysilane.
4. The inorganic-organic hybrid coating according to claim 1, characterized in that: In the component B, the vinyl trialkoxysilane is vinyl trimethoxysilane or vinyl triethoxysilane; and the γ-methacryloxypropyl trialkoxysilane is γ-methacryloxypropyl trimethoxysilane or γ-methacryloxypropyl triethoxysilane.
5. The inorganic-organic hybrid coating according to claim 1, characterized in that: The functional additives are defoaming agents, wetting and leveling agents, anti-sagging agents, and hand feeling agents.
6. An insulating coating for a battery cell, characterized in that: Comprising the inorganic-organic hybrid coating as claimed in claim 1.
7. The insulating coating for a battery cell according to claim 6, characterized in that: The insulation withstand voltage of the battery cell with the insulation coating is ≥3500V DC, 60 s; the leakage current is <0.1 mA; and the bonding strength with the structural adhesive is >10 Mpa.
8. A method for preparing an insulating coating for a battery cell as claimed in claim 6, characterized in that: The steps include: Step S1, pre-preparing component A and component B; Step S2, mixing, stirring and curing to obtain an inorganic-organic hybrid coating; Step S3, coating an inorganic-organic hybrid coating on the aluminum plate of the battery cell, and curing the coating to form an insulating coating for the battery cell.
Citation Information
Patent Citations
Insulation environment friendly paint for non-oriented electrical steel
CN101358096A
Method for preparing hydroxyl acrylic acid water dispersoid
CN101457005A
Inorganic-organic hybrid coating for rail transit and preparation method thereof
CN113913039A